2001
DOI: 10.1088/0029-5515/41/10/308
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic divertor experiments on the route to steady state operation of Tore Supra

Abstract: Ergodic divertor operation on Tore Supra is characterized by good performance in terms of divertor physics. Control of particle recirculation and impurity screening are related to the symmetry, both poloidally and toroidally, of the shell of open field lines and to its radial extent, ∆r ≈ 0.16 m. Feedback control of the divertor plasma temperature has led to controlled radiative divertor experiments. In particular, good performance is obtained when the plasma is controlled to be at a temperature comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The TEXTOR helical divertor is one such configuration, which continues earlier RMP related research, e.g. at Tore Supra with its ergodic divertor [1][2][3][4][5]. As a result of RMP application at TEXTOR, a 3D open chaotic magnetic field structure with helical strike lines is generated at the plasma edge [6][7][8], similar to the magnetic structure of divertors in stellarators such as LHD [9,10].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The TEXTOR helical divertor is one such configuration, which continues earlier RMP related research, e.g. at Tore Supra with its ergodic divertor [1][2][3][4][5]. As a result of RMP application at TEXTOR, a 3D open chaotic magnetic field structure with helical strike lines is generated at the plasma edge [6][7][8], similar to the magnetic structure of divertors in stellarators such as LHD [9,10].…”
Section: Introductionmentioning
confidence: 74%
“…Following the definition of detachment in [3] for the ergodic divertor at Tore Supra: "departure from the high-recycling regime", this latter regime at n sepx ≥ 3.5 can be regarded as detachment.…”
Section: Characteristics Of the Total Recycling Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Originally, the ergodic limiter was proposed as a procedure to obtain a uniform distribution of the exhausted power on the wall. 10,[21][22][23] The field line ergodization resulting from the resonant perturbation created by such a divertor would lead to a broadening of the scrape-off layer and a widening of the contact zone between plasma and the wall. 24 Devices based on this concept have been tested on several machines.…”
Section: Introductionmentioning
confidence: 99%
“…24 Devices based on this concept have been tested on several machines. 19,[21][22][23][25][26][27] However, further experiments have revealed that the heat and particle deposition patterns are not actually uniform as previously assumed, but are rather strongly structured, presenting a self-similarity that suggests an underlying fractal structure. [28][29][30][31][32][33][34][35] These structured patterns of the heat and particle deposition turn out to be undesirable from the point of view of controlling plasma-wall interactions, and have been investigated in a series of experiments with the dynamic ergodic divertor.…”
Section: Introductionmentioning
confidence: 99%